Análise do discurso de divulgação de ciência por meio da internet: uma reflexão sobre a relação entre a tecnologia e a academia - Medeiros, Marcelo (2008)
This work was born of concern experienced by a university professor of computer science as it passes to attend the master in science of language, experiences and the consequent fall of paradigms resulting from the interaction with the disciplines of analysis of speech and speech of dissemination of science. This work is based therefore on the analysis of discourse as a method of reflection on the texts of the websites to disseminate science. Through the cutting of some of these sites, there will be an analysis of the meanings of science that they are predominant. The proposed dissertation is still a draft proposal for an internet site for dissemination of science that enhances the position of the scientist-subject, allowing the creation of a shared memory and dynamic discourse